1976
DOI: 10.2466/pr0.1976.38.3c.1023
|View full text |Cite
|
Sign up to set email alerts
|

Objective Psychological Measurement and Alcoholism: Review of Literature, 1971–72

Abstract: The literature published in 1971 and 1972 on alcoholics in the United States was reviewed for objective psychological test data or behavioral measurements. The review was organized to facilitate further research by assembling information according to problem area and by including tests employed, significant findings ( p = .05), critical comments, and inferences for therapy. An appendix of references from 1968–1970 employing objective psychological measurements is included and cross-indexed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The MMPI (Hathaway & McKinley, 1940) has been the most frequently used personality instrument in the study of alcoholics (Knox, 1976). This research has provided a number of findings that are suggestive of a variety of personality subtypes within the 29 I alcoholic population.…”
mentioning
confidence: 99%
“…The MMPI (Hathaway & McKinley, 1940) has been the most frequently used personality instrument in the study of alcoholics (Knox, 1976). This research has provided a number of findings that are suggestive of a variety of personality subtypes within the 29 I alcoholic population.…”
mentioning
confidence: 99%
“…The total score can be ordered along a scoring continuum for assessment (Skinner, 1979), or it can be referred to a recommended cut-off for screening problem drinkers (Selzer, 1971). Several recent reviews of the MAST (e.g., Jacobson, 1976;Knox, 1976Knox, , 1978Miller, 1976) have concluded that the test has promise and that continued research toward improved standardization and validation is warranted.The MAST, similar to many alcoholism detection instruments and drinking problem surveys, assesses problems with alcohol without reference to specific dates of occurrence. Temporal parameters such as time of onset, duration, and most recent occasion for problems are omitted.…”
mentioning
confidence: 99%
“…Again, these problems may well be aspects of a more generalized confusion in mature adult roles. In an era of major changes in sex-role expectancies, the research may well be dated (Knox, 1976). Indeed, the current confusion and ambiguity in cultural definitions of sex roles may have implications for alcohol abuse.…”
Section: Defensive Denial or Ambivalencementioning
confidence: 99%
“…This will involve a consideration of the concept of etiology, and of some current issues in "mainstream" personality and social psychology. Previously published reviews of the literature in various types of relationships of individual differences and alcohol use will not simply be duplicated (see Sutherland, Schroder and Tordella, 1950;Syme, 1957;Armstrong, 1958;Lisansky, 1960Lisansky, , 1967Blum, 1966;Roebuck and Kessler, 1972;Braucht, Brakarsh, Follingstad and Berry, 1973;Kohn, 1974;Beckman, 1975;Hoffman, 1976;Sugerman and Schneider, 1976;Knox, 1976;Miller, 1976;O'Leary and O'Leary, 1976;Smart, 1976;Zimering and Calhoun, 1976;Williams, 1977). Rather, a critical overview of the current status of theory and research in the area will be provided.…”
mentioning
confidence: 99%